Patient navigation programs for people with dementia, their caregivers, and members of their care team: a scoping review protocol. Issue 1 (26th January 2022) - Doucet, Shelley; Luke, Alison; Anthonisen, Grailing; Kelly, Katherine J.; Goudreau, Alex; MacNeill, A. Luke; MacNeill, Lillian
ABSTRACT: Objective: The objective of this review is to map the literature on the characteristics, barriers, and faciliators of patient navigation programs for people with dementia, their caregivers, and/or members of their care team across all settings. Introduction: Patient navigation refers to a model of care that helps guide people through the health care system, matching their unmet needs to appropriate resources, services, and programs. Patient navigation may be beneficial to people with dementia because this is a population that frequently faces fragmented and uncoordinated care and has individualized care needs. Inclusion criteria: This review will focus on patient navigation programs for people living with dementia, their caregivers, and/or members of their care team, while excluding programs that do not explicitly focus on dementia. It will include patient navigation across all settings, delivered in all formats, and administered by all types of navigators, as long as the program is aligned with this article's definition of patient navigation, while excluding case management. Methods: This review will be conducted in accordance with JBI methodology for scoping reviews. The MEDLINE, CINAHL, PsycINFO, Embase, and ProQuest Nursing and Allied Health databases will be searched for published articles. Two independent reviewers will screen articles for relevance against the inclusion criteria. The results will be presented in a Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews flow diagram, and the extracted data will be presented in both tabular and narrative format.